Voyagers [videorecording (DVD)] - Burger, Neil; Sheridan, Tye, 1996-; Depp, Lily-Rose, 1999-; Whitehead, Fionn, 1997-; Farrell, Colin, 1976- (Lionsgate, 2021)
With the future of the human race at stake, a group of young men and women, bred for intelligence and obedience, embark on an expedition to colonize a distant planet. But when they uncover disturbing secrets about the mission, they defy their training and begin to explore their most primitive natures. As life on the ship descends into chaos, they are consumed by fear, lust, and the insatiable hunger for power.